2016
DOI: 10.1177/0888406416664184
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Practice

Abstract: Novice teachers need to develop foundation teaching skills to effectively address student behavior and academics in the classroom. The TLE TeachLivE™ simulation laboratory (TLE) is a virtual classroom used to supplement traditional didactic instruction and field experiences in teacher preparation programs. In this study, repeated practice and structured feedback were provided to preservice special educators in TLE to improve their delivery of specific praise, praise around, and error correction. Their weekly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 27 publications
2
29
0
2
Order By: Relevance
“…Austin is a male student with ASD who has limited verbal and cognitive abilities and is able to display typical characteristics of ASD such as rocking, flapping, moaning, and inattention. In contrast to Garland et al (2012), but like Dawson and Lignugaris/Kraft (2017), the current study measured the teachers’ ability to transfer their newly acquired skills to a real classroom. This study extended the research by including maintenance probes up to 8 weeks after the conclusion of coaching in the TeachLivE lab.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Austin is a male student with ASD who has limited verbal and cognitive abilities and is able to display typical characteristics of ASD such as rocking, flapping, moaning, and inattention. In contrast to Garland et al (2012), but like Dawson and Lignugaris/Kraft (2017), the current study measured the teachers’ ability to transfer their newly acquired skills to a real classroom. This study extended the research by including maintenance probes up to 8 weeks after the conclusion of coaching in the TeachLivE lab.…”
mentioning
confidence: 95%
“…Second, mixed-reality environments enable teachers to practice the application of, and experiment with, learned techniques in a safe, carefully controlled, realistic environment, decreasing the loss of potential student learning time while teachers are perfecting their skills (Garland, 2012; Hixon & So, 2009). One mixed-reality environment that has demonstrated the capacity to prepare teachers for the classroom is TLE TeachLivE ™ (TeachLivE; see Dawson & Lignugaris/Kraft, 2017; Garland, Holden, & Garland, 2016; Garland et al, 2012). TeachLivE is a learning lab designed to provide educators a place to practice teaching with virtual characters (avatars) manipulated by human performers (interactors) in a realistic mixed-reality setting in which interactions occur in real time and can be scripted or spontaneous (TLE TeachLivE ™ , 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this increase in task demand increased the variability in Shelly’s performance within practicum and across practicum settings. Dawson and Lignugaris/Kraft (2016) observed a similar decrease in targeted skill performance as more complex instructional routines were added to teacher’s repertoires. They suggested that modifying the order in which skills are introduced and the feedback structure might help new teachers maintain previous instructional skills when new skills are introduced.…”
Section: Complicating Factorsmentioning
confidence: 66%
“…This is because beyond making discrete practices accessible for learners, they even allow for highlighting multiple, alternative versions of a specific situation. In their potential to bring specific cases into teacher education, FVCs also relate to current, simulation-based pedagogical approaches such as TeachLive TM [19]. However, FVCs are not interactive, i.e., they do not allow learners to slip into the teacher role and directly interact with a simulated parent in an immersive environment.…”
Section: Introductionmentioning
confidence: 99%